2009
DOI: 10.1097/ta.0b013e31815edefd
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic Brain Injury After Frontal Crashes: Relationship With Body Mass Index

Abstract: Obese passengers are more likely to suffer a more severe head trauma after a frontal collision. Further studies with computational models are needed to determine the precise role of BMI on brain injury-related biomechanical metrics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
24
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(26 citation statements)
references
References 9 publications
2
24
0
Order By: Relevance
“…At a specific force level, side impacts induce 25% greater angular kinematics than frontal impacts (Hodgson et al, 1983). Thus, the anatomical shape of the human head and variations in the mass moments of inertia may be potential factors in injury susceptibility to side impacts; its inertia is approximately 1/3 lower in the coronal than in the sagittal plane (Tagliaferri et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…At a specific force level, side impacts induce 25% greater angular kinematics than frontal impacts (Hodgson et al, 1983). Thus, the anatomical shape of the human head and variations in the mass moments of inertia may be potential factors in injury susceptibility to side impacts; its inertia is approximately 1/3 lower in the coronal than in the sagittal plane (Tagliaferri et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…28 Many of the previous studies have investigated only injury incidence and mortality, with only a few exploring how specific occupant parameters affect MVC-associated brain injury. 4 The largest SDH volumes are seen in far-side crashes, but there are fewer correlations with crash parameters and occupant characteristics that are statistically significant, which may be related to the relatively small sample for this particular crash type. However, it is also possible that a greater sample size will be able to better predict the range of likely values, as well as anticipated clinically important correlations between dependent measures and crash variables.…”
Section: Discussionmentioning
confidence: 99%
“…1 Many studies have been conducted to investigate the epidemiology of TBI using databases such as the Crash Injury Research and Engineering Network (CIREN) and the National Automotive Sampling System (NASS) database. [2][3][4][5][6] The CIREN database contains detailed vehicle, crash, and medical data on injured MVC vehicle occupants. 7 It contains pre-crash information, along with detailed scene and vehicle investigation, medical images, and injury causation scenario and patient outcome.…”
mentioning
confidence: 99%
“…For example, Tagliaferri et al (2009) found a significant increase in fatality risk with obesity. Funk et al (2021) found an increase in fatality risk with increasing BMI, lack of seatbelt use and older aged occupants.…”
Section: Discussionmentioning
confidence: 96%